ANALYSIS OF SOCIOBUSINESS BEHAVIOR LEVEL OF BUSINESS PARTNERS (CASE STUDY AT OMNI CHANNEL STORE MUSTIKA KAYU PONCOKUSUMO BROMO MALANG) - Nilawati Fiernaningsih; Pudji Herijanto; Anna Widayani; Achmad Zaini; Maskur Maskur; Ismanto Ismanto (Jurnal Ekonomi, 2023)
The wooden craft industry in the Poncokusumo area, Bromo, has a wealth of historical and cultural value for Indonesian people. Apart from that, this industry also has potential as a micro business actor that can contribute to the local economy. It is crucial to understand how the behavior of groups of wood craftsmen influences cooperation, innovation, and the resulting social and economic impacts. This research aims to analyze the socio-business behavior of wood artisans at the Mustika Kayu omni channel shop in Pandansari Village, Poncokusumo District, Malang Regency. The study was carried out in July 2023, involving 30 wood artisans. Data was collected using a questionnaire and analyzed using quantitative descriptive data analysis methods. The research results show that pride in the group, mutual trust between group members, and more behavior towards the group positively influence the creation of a productive, harmonious, and collaborative work environment. This research guides wood artisans and other stakeholders in developing sustainable business practices that positively impact the local economy and community. This research has the potential to provide benefits for the development of the woodworking industry within a socio-business framework and contribute to more inclusive economic and social development in Poncokusumo and its surroundings.